Fiber yarn and preparation method thereof, fiber reinforced grinding stone and preparation method thereof
By using the preparation method of fiber yarn, the inorganic abrasive is evenly dispersed by using a single-component polyurethane aqueous emulsion and an alcohol solvent, which solves the problem that existing non-woven fabric brushes are prone to scratches, holes and pits when grinding PCB boards or plug selection boards, and achieves an efficient and uniform grinding effect.
Patent Information
- Application Number
- CN202411946420.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
Existing non-woven brushes can easily cause scratches, holes and pits when grinding PCB boards or plug selection boards, and the abrasives are prone to clumping and difficult to distribute evenly.
The preparation method of fiber yarn is adopted, in which the fibers are directly attached to sand, and the inorganic abrasive is uniformly dispersed by a single-component polyurethane aqueous emulsion and an alcohol solvent to form a small-sized fiber yarn to avoid scratches and hole blockages.
It is realized that the fiber yarn is not easy to break in whole pieces during grinding, avoid scratches and holes on the product, and improves the synchronization and consistency of the grinding.
Smart Images

Figure BDA0005213763030000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grinding materials, and in particular to fiber yarn and a preparation method thereof, a fiber reinforced grinding stone and a preparation method thereof. Background Art
[0002] Grinding metal or non-metal products to improve the surface properties of materials is a conventional technology, such as grinding products to achieve product surface thinning and roughening requirements. The surface treatment requirements of some conventional products are not high, and most conventional grinding stones can meet the requirements. As for the grinding on PCB boards or plug-in boards, since these boards have holes and the edges of the holes are concave, hard grinding stones such as ceramic brushes cannot grind to the concave parts. The existing solution is to use non-woven brushes for grinding. Although non-woven brushes can grind PCB boards and plug-in boards, they still have many disadvantages.
[0003] However, there are several major disadvantages in the manufacture of this type of brush, including scratching, clogging and pitting;
[0004] (1) Cause scratches
[0005] Since the non-woven brush is usually made by air-forming nylon fibers into a web, weaving it into a web and then soaking it in glue to shape it into a cloth, and then sandblasting or rolling glue. This sanding method is inferior, and high-speed sandblasting is used, the spraying thickness is difficult to control, and the abrasive is easy to clump, so it is easy to scratch the product during grinding.
[0006] (2) Blocking holes and pits
[0007] Non-woven brushes are usually made by adding glue to semi-finished non-woven fabric woven into a mesh. The non-woven fabric of this kind of grinding stone is integrated, and it is easy to fall off in a lump during grinding instead of being ground into fine powder. Therefore, it is easy to cause blockage of holes, or fall on the board, causing secondary crushing into pits, resulting in a short circuit in the circuit. Summary of the invention
[0008] Based on the above problems, the purpose of the present invention is to provide a fiber yarn and a preparation method thereof, a fiber-reinforced grinding stone and a preparation method thereof. The fiber yarn adopts a method of directly attaching sand to the fiber, and the inorganic abrasive is evenly dispersed and does not form a clumping, which can avoid scratches and damage to the surface of the grinding product. The fiber yarn of the fiber-reinforced grinding stone will not break off as a whole during grinding, and will not cause blockage or pits in the product.
[0009] To achieve the above-mentioned purpose, the first aspect of the present invention provides a fiber yarn, which is prepared by raw materials including, by weight, 20 to 40 parts of polymer fibers with a length of 2 to 5 mm, 40 to 60 parts of a single-component polyurethane aqueous emulsion, 0.5 to 1.0 parts of a coupling agent, 10 to 20 parts of a co-solvent and 40 to 60 parts of an inorganic abrasive, wherein the co-solvent includes an alcohol solvent.
[0010] In the technical solution adopted by the present invention, a single-component polyurethane aqueous emulsion is used as a sizing material for preparing raw materials. The contact angle of the solvent water to the inorganic abrasive is small and it is easy to be wetted, so the inorganic abrasive will not agglomerate, but will be separated by water to form single particles. Under the action of alcohol solvent and water, the components of the raw materials will form a uniform system. Combined with the action of the coupling agent, the single-particle inorganic abrasive will be evenly dispersed on the polymer fiber. Small-sized polymer fibers of 2 to 5 mm are directly attached with sand, so that small-sized fiber yarns with uniform abrasive distribution are obtained, which can avoid the problem of product scratches caused by abrasive agglomeration, and can also help improve the synchronization and consistency during subsequent grinding.
[0011] As a technical solution of the present invention, the transverse dimension of the polymer fiber is 10 to 20 μm.
[0012] As a technical solution of the present invention, the polymer fiber includes at least one of polyvinyl alcohol fiber, polyethylene fiber, polypropylene fiber, polyester fiber, polyamide fiber and polyvinyl chloride fiber.
[0013] As a technical solution of the present invention, the solid content of the one-component polyurethane aqueous emulsion is 5-10wt.%, and the viscosity is less than 200cps at 25°C.
[0014] As a technical solution of the present invention, the one-component polyurethane aqueous emulsion includes an aromatic isocyanate aqueous emulsion, an aliphatic isocyanate aqueous emulsion or an alicyclic isocyanate aqueous emulsion.
[0015] As a technical solution of the present invention, the coupling agent includes a silane coupling agent, a titanate coupling agent or an aluminate coupling agent.
[0016] As a technical solution of the present invention, the alcohol solvent includes at least one of ethanol, isopropanol, propylene glycol methyl ether, n-butanol and ethylene glycol.
[0017] As a technical solution of the present invention, the Dv50 of the inorganic abrasive is 1 to 120 μm.
[0018] As a technical solution of the present invention, the inorganic abrasive includes at least one of silicon carbide, aluminum oxide, silicon dioxide and boron nitride.
[0019] The second aspect of the present invention provides a method for preparing fiber yarn, comprising the steps of: mixing the polymer fiber, the single-component polyurethane aqueous emulsion, the coupling agent, the co-solvent and the inorganic abrasive, filtering to obtain a filter cake, drying the filter cake and removing excess abrasive using an ultrasonic vibrating screen to obtain fiber sand.
[0020] The preparation method of the present invention uses polymer fibers with a length of 2 to 5 mm, a single-component polyurethane aqueous emulsion, and an inorganic abrasive for mixing and dispersing. During the mixing process, the inorganic abrasive is easily wetted by water and adsorbed around the small-sized polymer fibers along with the single-component polyurethane aqueous emulsion. After filtration and drying to remove water, the excess abrasive is removed by screening. Finally, the polyurethane glue and the inorganic abrasive are loaded on the small-sized polymer fibers. The fiber yarn obtained in this way has a good filling effect of the inorganic abrasive and does not agglomerate. It can be used in a grinding stone to avoid damage to the product.
[0021] As a technical solution of the present invention, the mixing is carried out in a mixer, and the stirring time is 4 to 6 hours.
[0022] As a technical solution of the present invention, the drying is carried out in an electric hot air oven, and the drying temperature is 100-120° C. and the drying time is 4-6 hours.
[0023] As a technical solution of the present invention, the ultrasonic vibration screen screens out abrasives of 30 to 50 mesh.
[0024] The third aspect of the present invention provides a fiber-reinforced grindstone. The raw materials for preparing the grindstone include, by weight, 70 to 90 parts of fiber sand, 20 to 30 parts of thermoplastic phenolic resin powder, 5 to 10 parts of epoxy resin powder, 0.5 to 3.0 parts of curing agent powder and 0.5 to 3.0 parts of other additives, wherein the curing agent powder accounts for 6 to 15% of the weight of the thermoplastic phenolic resin powder, and the fiber sand is the aforementioned fiber yarn or the fiber yarn prepared by the aforementioned fiber yarn preparation method.
[0025] The fiber-reinforced grinding stone of the present invention uses thermoplastic phenolic resin powder and epoxy resin powder as sizing materials, and a combination of rigid resin and flexible resin can improve grinding efficiency and wear resistance. The fiber yarns with uniformly dispersed abrasives are connected by sizing materials, and the bonding strength is high. During grinding, the fiber yarns will not be worn away as a whole. Even if they fall off, they are fiber yarns wrapped in sizing materials, and the size is small, which is not easy to cause the product (such as PCB board or plug board) to block holes. The curing agent powder is 6-15% of the weight of the thermoplastic phenolic resin powder. By controlling the content of the curing agent powder, it is possible to avoid the thermoplastic phenolic resin powder and epoxy resin powder from curing too quickly, causing poor fluidity, and preventing the components of the entire system from being fixed before they have time to wet, resulting in poor overall uniformity and poor synchronous shedding, which will cause the product to have high roughness, scratches, and pits during grinding.
[0026] As a technical solution of the present invention, the Dv50 of the thermoplastic phenolic resin powder is 5 to 50 μm and the softening point is 95 to 110° C.
[0027] As a technical solution of the present invention, the epoxy resin powder has a Dv50 of 1 to 20 μm and a softening point of 95 to 110°C.
[0028] As a technical solution of the present invention, the epoxy resin powder comprises bisphenol A epoxy resin and / or phenol-type novolac epoxy resin.
[0029] As a technical solution of the present invention, the Dv50 of the curing agent powder is 1 to 20 μm.
[0030] As a technical solution of the present invention, the other auxiliary agents include at least one of a catalyst, a surfactant, a pigment and an anti-settling agent.
[0031] As a technical solution of the present invention, the components of the curing agent powder include at least one of aromatic amines, imidazoles, imidazole derivatives, dicyandiamide, dicyandiamide derivatives and polycyclic intra-cyclic tertiary amine compounds.
[0032] As a technical solution of the present invention, the components of the curing agent powder include at least one of 4,4′-diaminodiphenylmethane, meta-phenylenediamine, meta-phenylenediamine, benzyldimethylamine, 4,4′-diaminodiphenyl sulfone, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, dicyandiamide and hexamethylenetetramine.
[0033] The fourth aspect of the present invention provides a method for preparing a fiber reinforced grindstone, comprising the steps of: mixing the fiber sand, the thermoplastic phenolic resin powder, the epoxy resin powder, the curing agent powder and the other additives in a mixer and then putting them into a mold, hot pressing and demolding, and then baking.
[0034] The preparation method of the invention mixes the components and then performs heat pressing, so that the fiber yarns can be tightly connected and have high bonding strength.
[0035] As a technical solution of the present invention, the mixer is a V-shaped mixer with a rotation speed of 10 to 20 r / min and a mixing time of 6 to 8 hours.
[0036] As a technical solution of the present invention, the hot pressing uses a hot press machine to press at 130-150° C. for 10-20 minutes to compress the material into a thickness of 0.5-0.8 times.
[0037] As a technical solution of the present invention, the baking is carried out in an electric hot air oven at 150-160° C. for 1-2 hours. DETAILED DESCRIPTION
[0038] The fiber-reinforced grinding stone of the present invention can grind metal or non-metal products to reduce thickness and roughen them, and is particularly suitable for surface grinding of PCB boards or plug-in boards. After the fiber-reinforced grinding stone is used to grind the PCB board or plug-in board, the PCB board or plug-in board not only has low surface roughness, but also does not leak the substrate, and has no scratches or pits on the surface.
[0039] The raw materials for preparing the fiber-reinforced grinding stone of the present invention include 70-90 parts of fiber sand, 20-30 parts of thermoplastic phenolic resin powder, 5-10 parts of epoxy resin powder, 0.5-3.0 parts of curing agent powder and 0.5-3.0 parts of other additives in parts by weight.
[0040] Among them, the fiber sand can be, but not limited to, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 86 parts, 88 parts, and 90 parts. Thermoplastic phenolic resin powder can be, but not limited to, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, and 30 parts. The Dv50 of the thermoplastic phenolic resin powder is 5 to 50 μm, and as an example, it can be, but not limited to, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, and 50 μm. The softening point of thermoplastic phenolic resin powder is 95-110°C, and as an example, it can be but not limited to 95°C, 98°C, 100°C, 102°C, 104°C, 106°C, 108°C, and 110°C. The epoxy resin powder can be but not limited to 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, and 10 parts. The Dv50 of the epoxy resin powder is 1-20μm, and as an example, it can be but not limited to 1μm, 3μm, 5μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, and 20μm. The softening point of epoxy resin powder is 95-110°C, and as an example, it can be but not limited to 95°C, 98°C, 100°C, 102°C, 104°C, 106°C, 108°C, and 110°C. The composition of epoxy resin powder includes bisphenol A epoxy resin and / or phenol-type novolac epoxy resin. The curing agent powder can be, but is not limited to, 0.5 parts, 1.0 parts, 1.5 parts, 2.0 parts, 2.5 parts, and 3.0 parts. The curing agent powder is 6 to 15% of the weight of the thermoplastic phenolic resin powder. As an example, the proportion of the curing agent powder can be, but is not limited to, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%. Controlling the curing agent powder to 6 to 15% of the weight of the thermoplastic phenolic resin powder can control the curing polymerization speed of the thermoplastic phenolic resin powder, such as curing at 150°C for 180 to 300 seconds. The content of the curing agent powder should not be too low, otherwise the reaction is too slow to affect the efficiency and waste energy; if the content is too high, the reaction is too fast, the wetting of the fiber sand is incomplete, resulting in uneven distribution of the fiber sand, and poor grinding synchronization and consistency. The Dv50 of the curing agent powder is 1 to 20 μm, and as an example, it can be, but is not limited to, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, and 20 μm. The components of the curing agent powder include at least one of aromatic amines, imidazoles, imidazole derivatives, dicyandiamide, dicyandiamide derivatives, and polycyclic intra-cyclic tertiary amine compounds. Further, the components of the curing agent powder include at least one of 4,4′-diaminodiphenylmethane, metaphenylenediamine, metaphenylenediamine, benzyldimethylamine, 4,4′-diaminodiphenyl sulfone, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, dicyandiamide, and hexamethylenetetramine.Other additives may be, but are not limited to, 0.5, 1.0, 1.5, 2.0, 2.5, or 3.0 parts. Other additives include at least one of a catalyst, a surfactant, a pigment, and an anti-settling agent. The catalyst may be tris-(dimethylaminomethyl)phenol or 2,4,6-tris(dimethylaminomethyl)phenol. The surfactant may be octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, sorbitan fatty acid ester, and the like. The anti-settling agent may be polyamide wax.
[0041] The preparation method of the fiber reinforced grinding stone of the present invention may include the steps of: mixing fiber sand, thermoplastic phenolic resin powder, epoxy resin powder, curing agent powder and other additives in a mixer and then putting them into a mold, hot pressing and demolding, and then baking. The mixer can be a V-type mixer with a rotation speed of 10 to 20 r / min and a mixing time of 6 to 8 hours. Hot pressing uses a hot press to press at 130 to 150° C. for 10 to 20 minutes to compress into a thickness of 0.5 to 0.8 times. Baking is baking in an electric hot air oven at 150 to 160° C. for 1 to 2 hours.
[0042] The inorganic abrasive in the fiber sand of the present invention has good filling effect and does not agglomerate, and can avoid damage to the product when used in the grinding stone. The raw materials for preparing the fiber yarn include 20 to 40 parts of polymer fibers with a length of 2 to 5 mm, 40 to 60 parts of a single-component polyurethane aqueous emulsion, 0.5 to 1.0 parts of a coupling agent, 10 to 20 parts of a cosolvent and 40 to 60 parts of an inorganic abrasive, by weight.
[0043] The content of polymer fiber can be, but not limited to, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, and 40 parts. The polymer fiber is a small-sized fiber. As an example, its length can be, but not limited to, 2 mm, 3 mm, 4 mm, and 5 mm. The inorganic abrasive is compounded to obtain a small-sized fiber yarn. Even if it falls off after subsequent grinding, it is in the form of small-sized particles and will not fall off in large pieces. The lateral size of the polymer fiber is 10 to 20 μm. As an example, the lateral size can be, but not limited to, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, and 20 μm. The polymer fiber includes at least one of polyvinyl alcohol fiber, polyethylene fiber, polypropylene fiber, polyester fiber, polyamide fiber, and polyvinyl chloride fiber.
[0044] The content of the one-component polyurethane aqueous emulsion can be, but not limited to, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, and 60 parts. The solid content of the one-component polyurethane aqueous emulsion is 5 to 10 wt.%, and as an example, it can be, but not limited to, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, and 10 wt.%. The viscosity of the one-component polyurethane aqueous emulsion is less than 200 cps at 25°C. The one-component polyurethane aqueous emulsion includes an aromatic isocyanate aqueous emulsion, an aliphatic isocyanate aqueous emulsion, or an alicyclic isocyanate aqueous emulsion. When heated to a certain temperature, the one-component polyurethane aqueous emulsion can undergo a polymerization reaction by itself and solidify without the participation of another component in the reaction.
[0045] The content of the coupling agent can be, but is not limited to, 0.5, 0.6, 0.7, 0.8, 0.9, or 1.0. The coupling agent includes a silane coupling agent, a titanate coupling agent, or an aluminate coupling agent. Further, the coupling agent includes silane coupling agent KH550, silane coupling agent KH560, silane coupling agent KH570, silane coupling agent KH171, silane coupling agent KH792, titanate coupling agent KR-TTS, titanate coupling agent KR-38S, titanate coupling agent KR-138S, titanate coupling agent KR-238S, Titanate coupling agent KR-7, titanate coupling agent KR-12, titanate coupling agent KR-9S, titanate coupling agent KB-44, aluminate coupling agent 151, aluminate coupling agent 168, aluminate coupling agent 181, aluminate coupling agent 201, aluminate coupling agent 211, aluminate coupling agent 221, aluminate coupling agent 231, aluminate coupling agent 241, aluminate coupling agent 251, aluminate coupling agent 261.
[0046] The content of the cosolvent can be, but is not limited to, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts. The cosolvent includes an alcohol solvent, and the alcohol solvent includes at least one of ethanol, isopropanol, propylene glycol methyl ether, n-butanol and ethylene glycol.
[0047] The content of the inorganic abrasive can be, but is not limited to, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, and 60 parts. The Dv50 of the inorganic abrasive is 1 to 120 μm, and as an example, it can be, but is not limited to, 1 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, and 120 μm. The inorganic abrasive includes at least one of silicon carbide, aluminum oxide, silicon dioxide, and boron nitride, and silicon carbide, aluminum oxide, silicon dioxide, and boron nitride can be solid structures or hollow structures.
[0048] The preparation method of fiber sand of the present invention may include the steps of: mixing polymer fiber, single-component polyurethane aqueous emulsion, coupling agent, cosolvent and inorganic abrasive, filtering to obtain filter cake, drying the filter cake and removing excess abrasive by ultrasonic vibration screen to obtain fiber sand. The mixing is carried out in a mixer, and the stirring time is 4 to 6 hours. The drying is carried out in an electric heating blast oven, and the drying temperature is 100 to 120° C., and the drying time is 4 to 6 hours. The ultrasonic vibration screen screens out abrasives of 30 to 50 mesh.
[0049] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0050] Part 1: Preparation of Fiber Sand
[0051] Example 1
[0052] This embodiment is a fiber sand, and the raw materials for preparation include, by weight percentage, 30 parts of polyamide fiber with a length of 2 mm and a transverse dimension of 15 μm, 50 parts of a single-component aromatic isocyanate aqueous emulsion with a solid content of 5 wt.% (viscosity of less than 200 cps at 25°C), 0.6 parts of silane coupling agent KH-560, 15 parts of anhydrous ethanol, and 40 parts of silicon carbide with a Dv50 of 60 μm. The preparation method of the fiber sand includes the following steps.
[0053] Polyamide fiber, single-component aromatic isocyanate aqueous emulsion, silane coupling agent KH-560, anhydrous ethanol and silicon carbide were mixed in a blender for 5 hours, filtered to obtain a filter cake, and dried in an electric blast oven at 120°C for 4 hours. After drying, an ultrasonic vibration screen was used to sieve out excess abrasive of 50 mesh to obtain fiber sand 1#.
[0054] Example 2
[0055] This embodiment is a fiber sand, and the raw materials for preparation include, by weight percentage, 25 parts of polyamide fiber with a length of 2 mm and a transverse dimension of 15 μm, 45 parts of a single-component alicyclic isocyanate type aqueous emulsion with a solid content of 8 wt.% (viscosity of less than 200 cps at 25°C), 1.0 part of titanate coupling agent KR-38S, 10 parts of n-butanol, and 55 parts of silicon carbide with a Dv50 of 60 μm. The preparation method of the fiber sand includes the following steps.
[0056] Polyamide fiber, single-component alicyclic isocyanate aqueous emulsion, titanate coupling agent KR-38S, n-butanol and silicon carbide were mixed in a blender for 6 hours, filtered to obtain a filter cake, and dried in an electric blast oven at 120°C for 4 hours. After drying, an ultrasonic vibration screen was used to sieve out excess abrasive of 50 mesh to obtain fiber sand 2#.
[0057] Example 3
[0058] This embodiment is a fiber sand, and the raw materials for preparation include, by weight percentage, 30 parts of polyamide fiber with a length of 2 mm and a transverse dimension of 15 μm, 50 parts of a single-component aromatic isocyanate aqueous emulsion with a solid content of 5 wt.% (viscosity of less than 200 cps at 25°C), 0.6 parts of silane coupling agent KH-560, 15 parts of anhydrous ethanol, and 40 parts of hollow alumina with a Dv50 of 80 μm. The preparation method of the fiber sand includes the following steps.
[0059] Polyamide fiber, single-component aromatic isocyanate aqueous emulsion, silane coupling agent KH-560, anhydrous ethanol and hollow alumina were mixed in a blender for 5 hours, filtered to obtain a filter cake, and dried in an electric blast oven at 100°C for 6 hours. After drying, an ultrasonic vibration screen was used to sieve out excess abrasive of 50 mesh to obtain fiber sand 3#.
[0060] Example 4
[0061] This embodiment is a fiber sand, and the raw materials for preparation include, by weight percentage, 30 parts of polyethylene fiber with a length of 4 mm and a transverse dimension of 18 μm, 50 parts of a single-component aromatic isocyanate aqueous emulsion with a solid content of 5 wt.% (viscosity of less than 200 cps at 25°C), 0.6 parts of silane coupling agent KH-560, 15 parts of anhydrous ethanol, and 40 parts of silicon carbide with a Dv50 of 60 μm. The preparation method of the fiber sand includes the following steps.
[0062] Polyethylene fiber, one-component aromatic isocyanate aqueous emulsion, silane coupling agent KH-560, anhydrous ethanol and silicon carbide were mixed in a blender for 5 hours, filtered to obtain a filter cake, and dried in an electric blast oven at 120°C for 4 hours. After drying, an ultrasonic vibration screen was used to sieve out excess abrasive of 50 mesh to obtain fiber sand 4#.
[0063] Part II: Preparation of fiber reinforced grinding stones
[0064] Example 5
[0065] This embodiment is a fiber reinforced grinding stone. The raw materials for preparation include 70 parts of fiber sand 1#, 25 parts of thermoplastic phenolic resin powder (Dv50 is 20μm, softening point is 110℃), 7 parts of bisphenol A epoxy resin powder (Dv50 is 35μm, softening point is 105℃), 0.4 parts of 4,4'-diaminodiphenylmethane (Dv50 is 10μm), 2.5 parts of hexamethylenetetramine (Dv50 is 15μm) and 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol. The preparation method of the fiber reinforced grinding stone includes the following steps.
[0066] Fiber sand 1#, thermoplastic phenolic resin powder, bisphenol A epoxy resin powder, 4,4-diaminodiphenylmethane, hexamethylenetetramine and 2,4,6-tris(dimethylaminomethyl)phenol were mixed in a V-type mixer at a speed of 12r / min for 6h, put into a mold after mixing, and compressed into a thickness of 0.8 times by hot pressing at 140℃ for 10min using a hot press, and baked in an electric hot air oven at 160℃ for 1h after hot pressing demolding.
[0067] Example 6
[0068] This embodiment is a fiber reinforced grinding stone. The raw materials for preparation include 70 parts of fiber sand 2#, 25 parts of thermoplastic phenolic resin powder (Dv50 is 20μm, softening point is 110℃), 7 parts of bisphenol A epoxy resin powder (Dv50 is 35μm, softening point is 105℃), 0.4 parts of 4,4'-diaminodiphenylmethane (Dv50 is 10μm), 2.5 parts of hexamethylenetetramine (Dv50 is 15μm) and 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol. The preparation method of the fiber reinforced grinding stone includes the following steps.
[0069] Fiber sand 2#, thermoplastic phenolic resin powder, bisphenol A epoxy resin powder, 4,4-diaminodiphenylmethane, hexamethylenetetramine and 2,4,6-tris(dimethylaminomethyl)phenol were mixed in a V-type mixer at a speed of 12r / min for 6h, put into a mold after mixing, and compressed into a thickness of 0.8 times by hot pressing at 140℃ for 10min using a hot press, and baked in an electric hot air oven at 160℃ for 1h after hot pressing demolding.
[0070] Example 7
[0071] This embodiment is a fiber reinforced grinding stone. The raw materials for preparation include 90 parts of fiber sand 3#, 20 parts of thermoplastic phenolic resin powder (Dv50 is 35μm, softening point is 105℃), 5 parts of phenol-type phenolic epoxy resin powder (Dv50 is 30μm, softening point is 100℃), 0.3 parts of 4,4-diaminodiphenylmethane, 0.4 parts of (Dv50 is 13μm), 2.0 parts of hexamethylenetetramine (Dv50 is 8μm) and 0.4 parts of tris-(dimethylaminomethyl)phenol. The preparation method of the fiber reinforced grinding stone includes the following steps.
[0072] Fiber sand 3#, thermoplastic phenolic resin powder, phenol-type phenolic epoxy resin powder, 4,4'-diaminodiphenylmethane, hexamethylenetetramine and tri-(dimethylaminomethyl)phenol were mixed in a V-type mixer at a speed of 18 r / min for 6 hours, put into a mold after mixing, and compressed into a thickness of 0.5 times by hot pressing at 140°C for 10 minutes using a hot press. After hot pressing and demolding, the mold was baked in an electric heated blast oven at 160°C for 1 hour.
[0073] Example 8
[0074] This embodiment is a fiber reinforced grinding stone. The raw materials for preparation include 70 parts of fiber sand 4#, 25 parts of thermoplastic phenolic resin powder (Dv50 is 20μm, softening point is 110℃), 7 parts of bisphenol A epoxy resin powder (Dv50 is 35μm, softening point is 105℃), 0.4 parts of 4,4'-diaminodiphenylmethane (Dv50 is 10μm), 2.5 parts of hexamethylenetetramine (Dv50 is 15μm) and 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol. The preparation method of the fiber reinforced grinding stone includes the following steps.
[0075] Fiber sand 4#, thermoplastic phenolic resin powder, bisphenol A epoxy resin powder, 4,4-diaminodiphenylmethane, hexamethylenetetramine and 2,4,6-tris(dimethylaminomethyl)phenol were mixed in a V-type mixer at a speed of 12r / min for 6h, put into a mold after mixing, and compressed into a thickness of 0.8 times by hot pressing at 140℃ for 10min using a hot press, and baked in an electric hot air oven at 160℃ for 1h after hot pressing demolding.
[0076] Comparative Example 1
[0077] This comparative example is a non-woven grinding stone, and the preparation method of the non-woven grinding stone includes the following steps.
[0078] A polyamide nonwoven fabric with 70 parts of silicon carbide with a Dv50 of 60 μm was immersed in a mixed solution of 25 parts of an aqueous phenolic resin emulsion with a solid content of 75 wt.%, 32.5 parts of deionized water and 37.5 parts of isopropyl alcohol, and then dried in an electric heated blast oven at 120° C. for 4 hours and then dried at 150° C. for 2 hours to obtain a nonwoven grinding stone.
[0079] Comparative Example 2
[0080] This comparative example is a fiber-reinforced grinding stone, and the raw materials for preparation include 70 parts of fiber sand 1#, 25 parts of thermoplastic phenolic resin powder (Dv50 is 20μm, softening point is 110℃), 7 parts of bisphenol A epoxy resin powder (Dv50 is 35μm, softening point is 105℃), 0.4 parts of 4,4'-diaminodiphenylmethane (Dv50 is 10μm), 5.0 parts of hexamethylenetetramine (Dv50 is 15μm) and 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol, in terms of weight percentage. The preparation method of the fiber-reinforced grinding stone includes the following steps.
[0081] Fiber sand 1#, thermoplastic phenolic resin powder, bisphenol A epoxy resin powder, 4,4-diaminodiphenylmethane, hexamethylenetetramine and 2,4,6-tris(dimethylaminomethyl)phenol were mixed in a V-type mixer at a speed of 12r / min for 6h, put into a mold after mixing, and compressed into a thickness of 0.8 times by hot pressing at 140℃ for 10min using a hot press, and baked in an electric hot air oven at 160℃ for 1h after hot pressing demolding.
[0082] The grinding stones prepared in Examples 5 to 8 and Comparative Examples 1 to 2 were subjected to relevant tests, and the results are shown in Table 1. A 2 mm thick drilled copper clad laminate was used as the test plate, a single brush grinder was used, and the test current was set to 1.5 A to test the grinding performance of the grinding stones prepared in Examples 5 to 8 and Comparative Examples 1 to 2. Among them, the copper removal amount was obtained by testing with a BM-C30 copper thickness tester, and the roughness was obtained by testing with a Mitutoyo roughness tester, and the appearance of the drilled copper clad laminate after grinding a certain number of times was observed.
[0083] Table 1 Performance test results of the grinding stones obtained in Examples 5 to 8 and Comparative Examples 1 to 2
[0084]
[0085] From the results in Table 1, it can be seen that the grinding stones of Examples 5 to 8 are used to grind the drilled copper-clad laminate, and the apparent performance of the hole, pits, and board surface effect is better, while the non-woven grinding stone of Comparative Example 1 has leakage of the substrate, pits, and local scratches. This is because the non-woven grinding stone of Comparative Example 1 is softer and has good adhesion, and it severely wears the edge of the hole of the drilled copper-clad laminate, which is easy to cause leakage of the substrate. It falls off into fiber blocks during grinding, which will cause pits and scratches.
[0086] Although Comparative Example 2 uses small-size polymer fibers of 2 to 5 mm in size to directly attach sand to obtain a small-size fiber yarn with uniform abrasive distribution, the content of the curing agent in the preparation of the grinding stone is too high, the curing time of the resin is accelerated, the fluidity becomes worse, and the fiber yarn is shaped before it can wet the entire fiber yarn. The overall uniformity is poor, and the synchronous shedding property is poor, resulting in high roughness and scratches, poor local strength, and uneven shedding of the grinding stone, resulting in pits on the surface of the drilled copper clad laminate.
[0087] By comparing Example 1 and Example 4, it can be seen that the copper removal amount and roughness of the grindstone using polyamide fiber are higher than those of the grindstone using polyethylene fiber. However, polyethylene fiber has higher flexibility and thus better wear resistance.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A fiber yarn, characterized in that: The raw materials include 20-40 parts of polymer fibers with a length of 2-5 mm, 40-60 parts of single-component polyurethane aqueous emulsion, 0.5-1.0 parts of coupling agent, 10-20 parts of auxiliary solvent and 40-60 parts of inorganic abrasive by weight, wherein the auxiliary solvent includes alcohol solvent.
2. The fiber yarn according to claim 1, characterized in that The invention comprises at least one of the following features (1) to (8): (1) The transverse dimension of the polymer fiber is 10 to 20 μm; (2) the polymer fiber comprises at least one of polyvinyl alcohol fiber, polyethylene fiber, polypropylene fiber, polyester fiber, polyamide fiber and polyvinyl chloride fiber; (3) The solid content of the one-component polyurethane aqueous emulsion is 5 to 10 wt.%, and the viscosity is less than 200 cps at 25°C; (4) The one-component polyurethane aqueous emulsion includes an aromatic isocyanate aqueous emulsion, an aliphatic isocyanate aqueous emulsion or an alicyclic isocyanate aqueous emulsion; (5) The coupling agent includes a silane coupling agent, a titanate coupling agent or an aluminate coupling agent; (6) The alcohol solvent includes at least one of ethanol, isopropanol, propylene glycol methyl ether, n-butanol and ethylene glycol; (7) The Dv50 of the inorganic abrasive is 1 to 120 μm; (8) The inorganic abrasive includes at least one of silicon carbide, aluminum oxide, silicon dioxide and boron nitride.
3. The method for preparing fiber yarn according to claim 1 or 2, characterized in that: The method comprises the following steps: mixing the polymer fiber, the single-component polyurethane aqueous emulsion, the coupling agent, the cosolvent and the inorganic abrasive, filtering to obtain a filter cake, drying the filter cake and removing excess abrasive by ultrasonic vibration sieve treatment to obtain fiber sand.
4. The method for preparing fiber yarn according to claim 3, characterized in that: Includes at least one of the following features ① to ③: ① The mixing is carried out in a mixer, and the stirring time is 4 to 6 hours; ② The drying is carried out in an electric blast oven, and the drying temperature is 100-120° C. and the drying time is 4-6 hours; ③ The ultrasonic vibration screen screens out abrasives with mesh sizes of 30 to 50.
5. A fiber reinforced grinding stone, characterized in that: In parts by weight, the preparation raw materials include 70 to 90 parts of fiber sand, 20 to 30 parts of thermoplastic phenolic resin powder, 5 to 10 parts of epoxy resin powder, 0.5 to 3.0 parts of curing agent powder and 0.5 to 3.0 parts of other additives, wherein the curing agent powder accounts for 6 to 15% of the weight of the thermoplastic phenolic resin powder, and the fiber sand is the fiber yarn described in any one of claims 1 to 2 or the fiber yarn prepared by the preparation method of the fiber yarn described in any one of claims 3 to 4.
6. The fiber reinforced grinding stone according to claim 5, characterized in that: The invention comprises at least one of the following features (I) to (V): (I) the thermoplastic phenolic resin powder has a Dv50 of 5 to 50 μm and a softening point of 95 to 110° C.; (II) the epoxy resin powder has a Dv50 of 1 to 20 μm and a softening point of 95 to 110° C.; (III) the epoxy resin powder comprises bisphenol A epoxy resin and / or phenol-type novolac epoxy resin; (IV) the Dv50 of the curing agent powder is 1 to 20 μm; (V) The other auxiliary agents include at least one of a catalyst, a surfactant, a pigment and an anti-settling agent.
7. The fiber-reinforced grinding stone according to claim 5, characterized in that: The curing agent powder comprises at least one of aromatic amines, imidazoles, imidazole derivatives, dicyandiamide, dicyandiamide derivatives and polycyclic intra-cyclic tertiary amine compounds.
8. The fiber-reinforced grinding stone according to claim 7, characterized in that: The curing agent powder comprises at least one of 4,4′-diaminodiphenylmethane, m-phenylenediamine, m-phenylenediamine, benzyldimethylamine, 4,4′-diaminodiphenyl sulfone, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, dicyandiamide and hexamethylenetetramine.
9. The method for preparing a fiber reinforced grindstone according to any one of claims 5 to 8, characterized in that: The method comprises the following steps: mixing the fiber sand, the thermoplastic phenolic resin powder, the epoxy resin powder, the curing agent powder and the other auxiliary agents in a mixer, putting the mixture into a mold, and baking the mixture after hot pressing and demoulding.
10. The method for preparing a fiber reinforced grinding stone according to claim 9, characterized in that: Includes at least one of the following features (i) to (iii): (i) The mixer is a V-shaped mixer with a rotation speed of 10 to 20 r / min and a mixing time of 6 to 8 h; (ii) the hot pressing is performed by a hot press machine at 130 to 150° C. for 10 to 20 minutes to compress the film into a thickness of 0.5 to 0.8 times; (iii) The baking is carried out in an electric hot air oven at 150-160° C. for 1-2 hours.
Citation Information
Cited By
Long-fiber composite abrasive brush wire and preparation method thereof
CN121018420A